Multi-frequency oscillations implement complex spatio-temporal patterns of inter-regional communication - Kim, Jung Young; Choi, Jee Hyun; Demian Battaglia (Korean Society for Brain and Neural Sciences (KSBNS) 2024, 2024)
Cognitive tasks require flexible communication between multiple brain regions, which may be facilitated by neural oscillations. Several studies have emphasized the role of transient oscillatory coherence in a specific frequency band (e.g. gamma) to mediate communication. However, oscillations in the brain occur simultaneously in multiple frequency bands, which dynamically cooperate to perform cognitive tasks. In this study, we systematically investigate multi-frequency oscillation patterns and their effect on inter-region communication by constructing computational spiking networks models of structurally coupled regions oscillating at different frequencies. We firstly identify multi-frequency oscillations patterns (MFOPs) that transiently emerge during spontaneous dynamics. Remarkably, we find that as an effect of inter-regional excitatory or inhibitory interactions, fast or slow frequencies oscillatory burst can arise in all regions, irrespective of their local resonance frequency. Secondly, we use information theoretical analyses to extract the Information Routing Patterns (IRPs) associated to MFOP. We reveal that the joint occurrence of different frequency oscillatory bursts leads to a boosting of directed information transfer. Therefore, the variety of possible MFOPs gives rise to a rich dictionary of emergent IRPs, in which the regions can exchange information multiple times in alternating directions different from the ones initially hardwired at the neuronal resonance level. Overall, our computational analyses predict that interacting faster and slower frequency oscillations can impact information routing in more complex ways than postulated by current theories of frequency-multiplexing via cross-frequency coupling. They also emphasize that inter-regional communication is an active computation, not limited to the passive reception of but also encompassing the active integration within the target region of multiple information chunks received at different times.